Innovation And Entrepreneurship For Competitiveness In The ASEAN: An Empirical Analysis - Hesty Aisyah; Nopriadi Saputra (Jurnal Ekonomi Pembangunan, 2021)
ASEAN economies face new challenges in achieving sustainable, inclusive development, namely entrepreneurial innovation, impacting ASEAN's competitiveness. This research investigates the relationship between the power of innovation, entrepreneurship, and national competitiveness at the ASEAN country level. This study also examines how innovation and entrepreneurship can affect a country's competitiveness and inclusive development. The results of the comparative analysis based on means-testing using an independent sample t-test at the ASEAN level show a significant difference between the group of countries with a low-medium level of innovation ability and the group of countries with a high level of innovation ability. High levels of innovation imply that these countries have high competitiveness, entrepreneurship, and inclusive development levels. Meanwhile, the regression and correlation analysis results show that several ASEAN countries have high national competitiveness due to high levels of innovation, entrepreneurship, and inclusive development. The findings of this study may help develop policies to boost national competitiveness in inclusive growth.